2012
DOI: 10.1007/s00709-012-0413-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of five species of subfamily Papaveroideae from the Western Himalayas

Abstract: During the present course, population-based meiotic studies were carried out on five species of subfamily Papaveroideae from selected localities of Kashmir and Himachal Pradesh in the Western Himalayas (India). Varied intraspecific chromosome counts were reported for the first time in Argemone mexicana and Meconopsis latifolia, both existing on 2n = 2x = 14. The x = 7, confirmed for the first time from the newly found diploid cytotype, is suggested to be the primary chromosomal basic number for the Meconopsis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Cathcartia species also have 2n = 2x = 14, supporting the ITS phylogeny that places them outside Papaver , rather than within Meconopsis . Karyotype studies of Meconopsis species suggest that all are polyploid (2n = 8–12x = 56–84) [81], [85], [86], [87], but see Kumar et al [88]. We suggest that the Meconopsis clade originated with the polyploid transition to 2n = 2x = 56, possibly via a tetraploid intermediate with 2n = 4x = 28 chromosomes that is now extinct.…”
Section: Discussionmentioning
confidence: 72%
“…Cathcartia species also have 2n = 2x = 14, supporting the ITS phylogeny that places them outside Papaver , rather than within Meconopsis . Karyotype studies of Meconopsis species suggest that all are polyploid (2n = 8–12x = 56–84) [81], [85], [86], [87], but see Kumar et al [88]. We suggest that the Meconopsis clade originated with the polyploid transition to 2n = 2x = 56, possibly via a tetraploid intermediate with 2n = 4x = 28 chromosomes that is now extinct.…”
Section: Discussionmentioning
confidence: 72%
“…2e) seems to be responsible for chromosomal bridges ( Fig. 2f; Kumar et al 2013). Multipolarity was also observed in several populations of A. maritima and A. vulgaris (Fig.…”
Section: Meiotic Abnormalitiesmentioning
confidence: 84%
“…The migration of one or a few chromosomes into the neighbouring meiocytes leads to the formation of hyper-/hypoploid cells (Figs 2a,b), syncyte formation, and even the cells with double the normal chromosome number (Fig. 2b) which ultimately result in the formation of unreduced pollen grains (for reviews, see : Falistocco et al 1995;Sheidai & Fadaei 2005;Ghaffari 2006;Fadaei et al 2010;Jeelani et al 2011;Kumar et al 2013), as observed in Artemisia species (Figs 2l-n). The formation of unreduced gametes is of evolutionary significance since it can lead to the arising of plants with higher ploidy level through polyploidization (Villeux 1985).…”
Section: Meiotic Abnormalitiesmentioning
confidence: 99%
“…The reason behind such failure in segregation might be in relation to impaired attachment of kinetochores to the spindle fibers (Nicklas and Ward 1994), or through late chiasma terminalization, especially in large-sized bivalents (Pagliarini 2000, Souza et al 2006. The chromatin stickiness, late or non-disjuncting bivalents and chromatinl laggards seem to be responsible for chromosomal bridges (Kumar et al 2013), but a more appropriate cause for its formation is heterozygous paracentric inversions (Sinha and Godward 1972). All these mentioned abnormalities lead to the abnormal microsporogenesis with the formation of dyads, triads, and tetrads with micronuclei, and polyads and ultimately result in the heterogenous-sized pollen grains and high pollen sterility.…”
Section: Meiotic Abnormalitiesmentioning
confidence: 99%